Teacher leadership in a high-quality practice - Lager, Karin (Frontiers in Education, 2025)
This study scrutinizes teacher leadership in high-quality practices identified as both relationship-building and successful from a leisure pedagogical perspective. These situations are characterized by interactions where activities can be initiated by either children or teachers. Previous research on teacher leadership in school-age educare settings indicates a dynamic interplay between the initiatives of teachers and children. Leadership in this specific context is examined through a dynamic lens, considering how time, space, and relationships are co-constructed within social contexts and institutional frameworks, building on ethnographical fieldwork. The scenarios analyzed are drawn from a study investigating spatial features in children’s leisure time at school-age educare settings. The findings highlight three key aspects of teacher leadership in high-quality practice: (1) teachers´ commitment to the program, children, and colleagues; (2) structured framing of the program; and (3) continuous evaluation.